Ukrainian Orthodox community - between Russia's war and European integration - Julia Korniichuk (Eastern Journal of European Studies, 2024)
The aim of this article is to examine the transformations that have occurred within the Ukrainian Orthodox community in response to Russia's war of aggression against Ukraine, within the broader context of Ukraine's aspirations for European integration. Specifically, it focuses on the changes and diversification of the overall perception of Europe as a political community and Ukraine's position within it, the conflicts arising from the implementation of this vision, and the adaptation of it within the church (using the example of the calendar reform introduced in 2023). The study primarily relies on contextual and discourse analyses of texts from the two largest Ukrainian Orthodox churches: the Ukrainian Orthodox Church (Moscow Patriarchate) and the Orthodox Church of Ukraine, as well as the inter-religious All-Ukrainian Council of Churches and Religious Organisations.